Nonvolcanic Carbon Dioxide Emission at Continental Rifts: The Bublak Mofette Area, Western Eger Rift, Czech Republic - Horst Kämpf; Alena Sophie Broge; Pouria Marzban; Masoud Allahbakhshi; Tobias Nickschick (Geofluids)
This study presents the results of gas flux measurements of cold, mantle-derived CO2 release at the Bublák mofette field (BMF), located inside of the N-S directed Počátky Plesná fault zone (PPFZ). The PPFZ is presently seismically active, located in the eastern part of the Cheb Basin, western Eger Rift, Central Europe. The goal of the work was to identify the linkage between tectonics and gas flux. The investigated area has a size of 0,43 km2 in which 1.115 locations have been measured. Besides classical soil CO2 gas flux measurements using the closed chamber method (West Systems), drone-based orthophotos were used in combination with knowledge of plant zonation to find zones of high degassing in the agriculturally unused part of the BMF. The highest observed soil CO2 gas flux is 177.926,17 g m-2 d-1, and the lowest is 0,28 g m-2 d-1. Three statistical methods were used for the calculation of the gas flux: arithmetic mean, kriging, and trans-Gaussian kriging. The average CO2 soil degassing of the BMF is 30 t d-1 for an area of 0,43 km2. Since the CO2 soil degassing of the Hartoušov mofette field (HMF) amounts to 23 t d-1 for an area of 0,35 km2, the average dry degassing values of the BMF and HMF are in the same magnitude of order. The amount of CO2 flux from wet mofettes is 3 t d-1 for the BMF and 0,6 t d-1 for the HMF. It was found that the degassing in the BMF and HMF is not in accordance with the pull-apart basin interpretation, based on the direction of degassing as well as topography and sediment fill of the suggested basins. En-echelon faults inside of the PPFZ act as fluid channels to depth (CO2 conduits). These structures inside the PPFZ show beginning faulting and act as tectonic control of CO2 degassing.